Adoption and Determinants of Mobile-based Agro-Advisory Services Among Farmers in Bharatpur Metropolitan City, Chitwan - Adhikari, Sulochana; Bhattarai, Milan; Karki, Sabin (Tribhuvan University Journal, 2026)
Mobile-Based Agro-Advisory Services (MBAAS) have emerged as an innovative tool to provide farmers with timely information on crop management, weather, pests, and markets. A study was conducted to examine the adoption and key factors influencing the use of mobile-based agro-advisory services among farmers in Bharatpur Metropolitan City, Chitwan. A total of 99 farmers were purposively sampled, and primary data were collected using a pre-tested semi-structured questionnaire, focus group discussions, and key informant interviews. Descriptive statistics, probit regression, and index score method were applied to analyse the data with the support of STATA version 14.2 and Ms Excel. Findings reveal that Facebook or You tube were more dominant over other platform, with crop management tips, pest and disease identification and Weather forecasts, were widely used. Lack of awareness, difficulty in understanding technical terms, and limited digital literacy emerged as major barriers to adoption. Years of education (0.024), Digital literacy score (0.049), primary occupation (0.199) and Age (0.011) significantly affect the adoption of mobile-based agro-advisory services. Future digital agricultural advisory should incorporative inclusive interventions for bridging gaps to reduce digital divide.